Another prefiltering algorithm for adaptive IIR filtering - Abud Marcelino, Marcio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1995)
An algorithm for adaptive IIR filtering that uses prefiltering structure in direct form is presented. This structure has an estimation error that is a linear function of the coefficients. This property greatly simplifies the derivation of gradient-based algorithms. Computer simulations show that the proposed structure improves convergence speed.
Keywords: Adaptive filtering; Computer simulation; Convergence of numerical methods; Digital filters; Error analysis; Errors; Estimation; Identification (control systems); Estimation error; Mean square error; Prefiltering algorithm; Algorithms